Wiezy krwi - Roberts, Nora.; Dobrzanska-Gadowska, Anna. (Warszawa : Swiat Ksiazki, 2003)
Polish translation of "Birthright". Callie Dunbrook, an archeologist, is working on a five thousand year old site in the Blue Ridge mountains of the US.
Keywords: Women archaeologists -- Fiction; Divorced women -- Fiction; Birthparents -- Fiction; Antietam Creek Region (Pa. and Md.) -- Fiction; Blue Ridge Mountains -- Fiction